Penyuluhan Mengenai COVID-19 dan Penyuluhan Bidang Digital Marketing - indriyani, susi; Hermawan, Nur Sefa Arief; Riskawati, Riskawati; Yuniarthe, Yodhi (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2023)
Counseling on COVID-19 focuses on providing accurate and up-to-date information about the coronavirus, preventive measures, health management, and efforts to break the chain of spread of the virus. The purpose of this outreach is to increase public awareness about COVID-19 and encourage healthy and safe behaviors. On the other hand, counseling in the field of digital marketing discusses marketing strategies and methods used in the digital era. In an increasingly connected business environment online, it is important for business people to understand how to leverage digital technology to promote their products or services. Counseling in this field covers topics such as social media, search engine optimization, use of digital platforms, data analysis, and other digital marketing strategies. This riset explains the importance of counseling about COVID-19 in the context of the current global pandemic and how digital marketing counseling can be used as a means to disseminate relevant information and help people and businesses in facing current challenges. The research also highlights effective strategies and approaches in delivering extension materials, both in the form of digital campaigns and appropriate digital marketing. Keywords: counseling, COVID-19, digital marketing, information, awareness, marketing strategy, social media, digital technology, pandemic.